KESALAHAN BERBAHASA DALAM DISKUSI KELOMPOK PEMBELAJARAN BAHASA INDONESIA SMK IMMANUEL 2 KUBU RAYA TAHUN PELAJARAN 2022/2023 - Bangga, Try Anugerah; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabi'ul (Universitas Tanjungpura, 2023)
This study aims to describe pronunciation, diction, and sentence structure errors in group discussions in learning Indonesian SMK Immanuel 2 Kubu Raya students. This study used qualitative descriptive design. The subject of this study was the pronunciatiation, diction, and sentence structure of leaners in group discussions. Data collection in using non-participant observation techniques, recording techniques, listening techniques,and recording techniques. The data obtained were analyzed using descriptive techniques. The results of this study showed that 104 sentences were found that contained errors, namely (1) pronunciation errors totaling 46 errors caused by Malay dialects and Pontianak Chaines, namely, phoneme changes, phoneme additions, and phoneme omissions, (2) diction errors totaling 28 errors due to improper word selection, and (3) sentence structure errors totaling 30 errors caused by limited vocabulary in delivering good and correct sentences.